Cultural Relativity in Perceiving Emotion From Vocalizations. (April 2014) - Gendron, Maria; Roberson, Debi; van der Vyver, Jacoba Marieta; Barrett, Lisa Feldman
A central question in the study of human behavior is whether certain emotions, such as anger, fear, and sadness, are recognized in nonverbal cues across cultures. We predicted and found that in a concept-free experimental task, participants from an isolated cultural context (the Himba ethnic group from northwestern Namibia) did not freely label Western vocalizations with expected emotion terms. Responses indicate that Himba participants perceived more basic affective properties of valence (positivity or negativity) and to some extent arousal (high or low activation). In a second, concept-embedded task, we manipulated whether the target and foil on a given trial matched in both valence and arousal, neither valence nor arousal, valence only, or arousal only. Himba participants achieved above-chance accuracy only when foils differed from targets in valence only. Our results indicate that the voice can reliably convey affective meaning across cultures, but that perceptions of emotion from the voice are culturally variable.